(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines the publication efficiency index, average citations per paper, authorship pattern, degree of collaboration, collaborative index, collaborative coefficient, modified collaborative coefficient, and application of Inverse-square law of global geese literature based on 4801 records retrieved from the Scopus database during the time frame 2008 to 2017. The study revealed that Publication Efficiency Indices and Average Citations Per Publications are more significant from 2008 to 2012. But after 2012 value of PEI is less than one, which indicates that the research impact of geese research publications is gradually decreasing year by year. Three authorship patterns dominate other authorship patterns by contributing 29.74% of articles and 18.89% of the author’s participation. The mean value of the Degree of collaboration is found to be 0.989, which implies that collaborative publications are remarkably dominating single-authored publications. Collaborative Index was topmost in 2016 with the value 5.275 since the total number of author participation per paper is the highest. The rate of CC and MCC is also monitored the largest in 2016 with 0.755 and 0.757 consecutively. Application of Inverse-square law and verification of Kolmogorov-Smirnov test disclosed that the scientific productivity of authors of geese research publication is well matched with the theoretical distribution of Inverse-square law.